Physical attractiveness and health in Western societies a review. [article]. - Weeden, J.
Evidence from developed Western societies is reviewed for the claims that (a) physical attractiveness judgments are substantially based on body size and shape, symmetry, sex-typical hormonal markers, and other specific cues and (b) physical attractiveness and these cues substantially predict health. Among the cues that the authors review, only female waist-to-hip ratio and weight appear to predict both attractiveness and health in the claimed manner. Other posited cues--symmetry and sex-typical hormonal markers among them--failed to predict either attractiveness or health (or both) in either sex. The authors find that there is some indication that attractiveness has an overall relationship with health among women, but little indication that male attractiveness relates to male health. -- (from the author)